THE EFFECT OF CRYSTALLIZER ROTATION ON THE GAS HYDRATE PERFORMANCES - Widya Wijayanti; Mega Nur Sasongko; Nurkholis Hamidy; Purnami Purnami (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2017)
The performance of hydrate was shown by the hydrate formation rate, the hydrate stability, and the storage capacity. In the study, we investigated the hydrate performance by influencing the rotation of crystallizer that predicted to increase the agitation of the hydrate performance. The hydrate represent the bond of water molecules and gas absorbed by the water molecules. In the experiment, we used the 50% propane and 50% butane as the gas absorbed. The gas was injected in a crystallizer at 3 bar pressure, then the crystallizer was rotated by 100, 200, and 300 rpm. The results shows that the best performances of hydrate when the crystallizer was rotated at 300 rpm. The crystallizer rotation speed of 300 rpm had the highest the formation rate and the decomposition rate. The highest decomposition rate indicated the highest stability. Meanwhile, the highest hydrate storage capacity was also occured at the rotation of 300 rpm as 2809 V / V.